Floristic-ecological diversity and syntaxonomy of plant communities dominated by Genista radiata in Italy. (2nd November 2022) - Viciani, D.; Lastrucci, L.
Abstract: Genista radiata is a dwarf/low orophilic shrub having a fundamentally southern European distribution. In Italy, it can be found in different ecological contexts, often giving rise to diversified coenoses. Due to its ecological plasticity, G. radiata communities have been considered sometimes as simple dynamic variants of grasslands aspects, sometimes as more or less stable shrublands and this interpretation has changed over time. The aim of this study was to analyze the coenological and ecological features of all Italian G. radiata communities. An Italian comprehensive data-set has been investigated by means of multivariate analysis. Ecological and chorological analyses were performed, and the diagnostic species of different groups were identified through the phi coefficient of association. According to our analysis, nine different types of G. radiata communities were found to be present in Italy. Each group was characterized by means of its floristic, ecological and chorological components and investigated as to its syntaxonomic aspects. This allowed us to attribute the Italian G. radiata communities to nine different associations, four of which already existing and five proposed as new or as stat. nov. Their classification at higher levels is discussed and a comprehensive syntaxonomic scheme is proposed. Supplemental data for this article is available online at https://doi.org/10.1080/11263504.2022.2056646.